2022
DOI: 10.1111/bju.15855
|View full text |Cite
|
Sign up to set email alerts
|

Cushioning the blow: role of perirenal fat in renal trauma injury severity

Abstract: This manuscript has not been published and is not under consideration for publication elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A recent paper revealed an inverse relationship between the thickness of the peri-renal fat and the occurrence of high-grade renal injuries. This relationship was not influenced by patients’ Body Mass Index and may be associated with their nutritional status [17].…”
Section: Text Of the Reviewmentioning
confidence: 78%
“…A recent paper revealed an inverse relationship between the thickness of the peri-renal fat and the occurrence of high-grade renal injuries. This relationship was not influenced by patients’ Body Mass Index and may be associated with their nutritional status [17].…”
Section: Text Of the Reviewmentioning
confidence: 78%
“…Tissue imaging study of other surrounding organs has received increasing attention. For example, perirenal fat thickness (PFT) is highly correlated with renal trauma grade ( 15 ), but it is often neglected in the imaging diagnosis of LSS patients and has not been reported. In magnetic resonance imaging studies of LSS combined with RNRs ( 6 , 13 , 16–18 ), it was shown that the sagittal and transverse diameters of the spinal canal at the level of maximal stenosis, the area of the dural sac, the thickness of the ligamentum flavum, and the presence or absence of disc herniation and lumbar spondylolisthesis contributed to the development of RNRs, and it was concluded that for female patients, the older they were, and the higher the degree of lumbar canal stenosis, the more likely they were to develop RNRs.…”
Section: Introductionmentioning
confidence: 99%